John's Other Practice - Marks, Winston K. (Winston Kinney), 1915-1979; Terry, W. E., 1921-1992 (Salt Lake City, UT : Project Gutenberg, 2021)
"John's Other Practice" by Winston K. Marks is a science fiction narrative written in the mid-20th century. The story revolves around the unconventional medical practices of John Cunningham, who has developed a series of slot-machine-like devices called "Symptometers," designed to provide health diagnostics in an entertaining format. With its blend of humor and critique on the medical profession, the book explores themes of ethics in medicine and the unintended consequences of technology. The plot follows Dr. Klinghammer, an investigator for the Malpractice Board, who is tasked with probing the complaints about these dubious machines, which purport to diagnose ailments in a fun but potentially misleading way. As he navigates through the bizarre world of Cunningham's inventions, Klinghammer becomes entangled in the lives of Cunningham and Dr. Sue Calicoo. Their relationships and intentions create a humorous yet poignant commentary on romantic entanglements while questioning the ethics of medical practices in a society increasingly influenced by technology. Ultimately, the narrative culminates in a resolution that touches on innovation, responsibility, and the blending of professional and personal lives. (This is an automatically generated summary.)
Release date is 2021-09-22
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Physicians -- Fiction; Man-woman relationships -- Fiction; Inventions -- Fiction